Quantitative µMRI and PLM study of rabbit humeral and femoral head cartilage at sub‐10 µm resolutions. Issue 5 (12th December 2019) - Batool, Syeda; Mahar, Rohit; Badar, Farid; Tetmeyer, Austin; Xia, Yang
ABSTRACT: This study aimed to establish the baseline characteristics in humeral and femoral cartilage in rabbit, using quantitative magnetic resonance imaging (MRI) relaxation times (T2, T1ρ, and T1) at 9.75 and 70–82 µm pixel resolutions, and quantitative polarized light microscopy (PLM) measures (retardation, angle) at 1.0 and 4.0 µm pixel resolutions. Five intact (i.e., unopened) shoulder joints (the scapula and humeral heads) and three femoral heads of the hip joints from five healthy rabbits were imaged in MRI at 70–82 µm resolution. Thirteen cartilage‐bone specimens were harvested from these joints and imaged in µMRI at 9.75 µm resolution. Subsequently, quantitative PLM study of these specimens enabled the examination of the fibril orientation and organization in both intact joints and individual specimens. Quantitative MRI relaxation data and PLM fibril structural data show distinct features in tissue properties at different depths of cartilage, different in individual histological zones. The thicknesses of the histological zones in µMRI and PLM were successfully obtained. This is the first correlated and quantitative MRI and PLM study of rabbit cartilage at sub‐10 µm resolutions, which benefits future investigation of osteoarthritis using the rabbit model. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:1052‐1062, 2020